Diseño de una estrategia comunicacional para el reposicionamiento de la empresa ARCADIN Consultora y Constructora S.A. - Barreto Quevedo, Ingri Pamela (2024)
The company ARCADIN Consultora y Constructora S.A.S. has more than a year offering its services to meet the needs of citizens; thanks to the so-called S.A.S., it has achieved growth in its portfolio of services and products with the implementation of new services. A communication strategy and digital marketing were implemented to position the new services and the company. The approach to be developed for the study is mixed, which facilitates the understanding of the various concepts. In the same way, the description of the processes was used for the development of the research. The project is intended to generate interest that will allow the company to develop and attract new audiences both in the province and at the national level, improving the company's positioning. It is vital to focus on the competitive advantages of the company and constantly analyze the competition; an analysis of the company was made, and the information collected was taken as a starting point for the approach of the appropriate communication strategy, always focusing on the target audience that helped the positioning. The final result of this positioning process allows the creation of a clear image of the productor services, managing to provide value to the consumer.